2017
DOI: 10.2739/kurumemedj.ms00014
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Ulcerative Colitis with Neurofibromatosis Type 1

Abstract: Concomitant association of histologically proven inflammatory bowel disease (IBD) and neurofibromatosis type 1 (NF1) is a rare finding documented in only 5 adult clinical cases. A 34-year-old woman with known neurofibromatosis was admitted to our department with a 6-month history of intractable bloody diarrhea and abdominal pain. After a thorough clinical examination and paraclinical assessments, including colonoscopy and biopsy, ulcerative colitis (UC) was confirmed as the cause of gastrointestinal bleeding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A review of the literature demonstrates 7 cases (4 female and 3 male) previously reported. [1][2][3][4][5][6] Five cases received a diagnosis of UC, and 2 a diagnosis of Crohn's disease. The mean age of onset of disease was 36 years, with only 2 cases reported in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature demonstrates 7 cases (4 female and 3 male) previously reported. [1][2][3][4][5][6] Five cases received a diagnosis of UC, and 2 a diagnosis of Crohn's disease. The mean age of onset of disease was 36 years, with only 2 cases reported in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…The literature available on the association of NF1 with IBD is limited to a small number of case reports, and none had comorbid PSC. [1][2][3][4][5][6] We present a review of the published literature on this rare association and add the findings of our patient.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve articles reported cases of IBD in subjects with other genetic syndromes (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Seven papers reported eight cases of IBD (three CD and five UC) in patients with NF1 (44)(45)(46)(47)(48)(49)(50), with two pediatric UC cases (48,49). Table 5 illustrates the characteristics and results of these studies.…”
Section: Clinical Features and Prevalence Of Ibd In Other Genetic Syndromesmentioning
confidence: 99%